ADDRESSING OPTIMISM AMONG THE YOUNG INDONESIAN GENERATION IN SUSTAINING THE PANDEMIC - Clara Evi Citraningtyas (Universitas Pendidikan Ganesha, 2021)
The COVID-19 pandemic has utterly devastated our world and has essentially influenced and disrupted people's lives. This condition has resulted in a rise in anxiety and depression, particularly among the young. In such a situation, optimism is essential. Because young people are valuable future assets, it is critical to address their optimism and devise measures to enhance it. This study aims to investigate the presence of optimism among Indonesian youth and how it is achieved. A total of 86 undergraduate students between the ages of 17 and 21 volunteered to participate. This study collects data through a survey and a Focus Group Discussion, using a mixed quantitative and qualitative approach. The findings show that most respondents were pessimistic and claimed that the pandemic harmed their lives, emotions, and future outlook. A limited number of respondents who expressed optimism in the survey were then invited to participate in a Focus Group Discussion, and they reported that their optimism is attained from internal (egocentric) and external (ethnocentric) factors. This finding is valuable and essential for taking action on how to help a generation afflicted by the pandemic move forward with optimism.